Implementasi Konsep Pembelajaran Dan Karakteristik Peserta Didik Abad 21 - Barus, Carolina Sri Athena; Asry N Latupeirissa; Dewilna Helmi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The development of the 21st century is marked as the century of openness or the century of globalization, meaning that human life in the 21st century has undergone fundamental changes that are different from the order of life and characteristics in the previous century. The purpose of this service activity is to implicate the Learning Concept and Characteristics of 21st Century Students, as facilitating learning. The methods used in this service include lectures, practices, and discussions. There are several stages in this service activity, namely coordination, and analysis of needs, preparation of materials and activities, training, monitoring, and evaluation, as well as data analysis and reports. The results of this service show an increase in the understanding of teachers after participating in the socialization of Learning Concepts and Characteristics of 21st Century Students, with an average understanding categorized as very good. This Community Service Activity (PKM) assists teachers in designing learning that is interesting and according to the needs of students in the 21st century, so that teachers can become more aware of the importance of the characteristics of students in the 21st century. It is hoped that the results of this community service can become a reference for other educational institutions as well as teachers are also more familiar with the needs of educators.